BENTUK PENILAIAN ASPEK PENGETAHUAN DALAM BUKU TEKS SISWA BAHASA INDONESIA SMA KURIKULUM 2013 - Desy Rufaidah (CARAKA, 2019)
The purpose of this research is to describe the assessment form of the knowledge aspects contained in the Indonesian High School Curriculum 2013 textbooks. The research data are phrases, words, clauses, sentences, paragraphs, and discourses that contain content about assessment forms of knowledge contained in the textbook. Data is obtained by documentation techniques then validated by expert judgment and FGD. Data is analyzed with interactive analysis techniques. The results of the research included assessment forms of knowledge aspects of class X and XI in Indonesian textbooks inÂ  Curriculum 2013. Assessment Forms of knowledge aspects of class X textbooks include entries, descriptions, question, and answer, and assignments while in class XI include multiple choices, incorrect, fill, description, and assignment.